1980
DOI: 10.1056/nejm198004103021504
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke in Asymptomatic Persons with Cervical Arterial Bruits

Abstract: A survey of the rural community in Evans County, Georgia, revealed cervical arterial bruits in 72 (4.4 per cent) of 1620 persons 45 years of age of older without previous stroke, transient ischemic attacks, or overt ischemic heart disease. The prevalence of such asymptomatic bruits increased with age and was greater in women and persons with hypertension. We estimated the risk of stroke associated with cervical bruits during a six-year follow-up period, taking age and blood pressure into account. The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
1
3

Year Published

1981
1981
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(49 citation statements)
references
References 12 publications
7
38
1
3
Order By: Relevance
“…The large numbers of persons aged 70 years and older in SHEP may explain the lack of association of carotid bruits with subsequent stroke in this cohort compared with previous population-based studies. [8][9][10] Our findings are consistent with those of Van Ruiswyk and colleagues, 11 who found that carotid bruits did not predict stroke (RR 1.1; 95% CI 0.45, 2.7) in a cohort of 241 frail nursing home residents aged 75 years or older. However, in addition to providing well-defined cohort and adjudicated end points, our study subjects more closely resemble patients who would be candidates for office screening-they were at increased risk of stroke, but otherwise were in relatively good health, and would have the most to lose from a catastrophic event.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The large numbers of persons aged 70 years and older in SHEP may explain the lack of association of carotid bruits with subsequent stroke in this cohort compared with previous population-based studies. [8][9][10] Our findings are consistent with those of Van Ruiswyk and colleagues, 11 who found that carotid bruits did not predict stroke (RR 1.1; 95% CI 0.45, 2.7) in a cohort of 241 frail nursing home residents aged 75 years or older. However, in addition to providing well-defined cohort and adjudicated end points, our study subjects more closely resemble patients who would be candidates for office screening-they were at increased risk of stroke, but otherwise were in relatively good health, and would have the most to lose from a catastrophic event.…”
Section: Discussionsupporting
confidence: 90%
“…Also, in one study center, SHEP examiners identified bruits in 8 (7.3%) of 109 participants; whereas a single observer, as a part of an ancillary study, detected 19 bruits in 99 (19.2%) of the members of the same cohort. 23 However, in SHEP the overall prevalence and location of bruits is similar to that in other studies, 9,10 suggesting that, however imprecise, our findings probably apply to the performance of neck auscultation in a typical clinical setting.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the general population, asymptomatic carotid bruits do not appear to greatly increase the risk of cerebral vascular disease (770,771). Although asymptomatic carotid bruits increase the risk of stroke after coronary artery bypass surgery, the increase in risk is probably small (772).…”
Section: Recommendationsmentioning
confidence: 99%